POPULATION OF THE CITY OF KOKAND IN THE LATE XIX – EARLY XX CENTURIES AND ITS GROWTH DYNAMICS (Scientific journal of the Fergana State University, 2023)
The article highlights the composition of the population of the city of Kokand, as well as the dynamics of its growth in the late XIX – early XX centuries on the basis of archival materials.